Rainfall inequality, political power, and ethnic conflict in Africa - Andrea Guariso; Thorsten Rogall (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2017)
Does higher resource inequality between ethnic groups lead to ethnic conflict? In this paper, we empirically investigate this question by constructing a new measure of inequality using rainfall on ethnic homelands during the plant-growing season. Our dataset covers the period 1982-2001 and includes 214 ethnicities, located across 42 African countries. The analysis at the country level shows that one standard-deviation increase in rainfall-based inequality between ethnic groups increases the risk of ethnic conflict by 16 percentage points (or 0.43 standard deviations). This relationship depends on the power relations between the ethnic groups. More specifically, the analysis at the ethnicity level shows that ethnic groups are more likely to engage in civil conflicts whenever they receive less rain than the leading group. This effect does not hold for ethnic groups that share some political power with the leading group and is strongest for groups that have recently lost power. Our findings are consistent with an increase in resource inequality leading to more ethnic conflicts by exacerbating grievances in groups with no political power.
Keywords: D63; D74; E01; 330; Conflict; Ethnic Inequality; Rainfall; Africa; Ethnic Power Relations